Linguistic and Psychological Features of Adjectives and Their Lexicographic Description Problem - Zhuykova, Marharyta (East European Journal of Psycholinguistics, 2018)
In the semantics of many adjectives (words that characterize various properties of the objects) a significant place belongs to the features that a person perceives through the perception organs. A psycholinguistic experiment with Russian native-speakers has been conducted. Within this experiment a significant group of nouns (more than 7.6 thousand units), which are directly related to one or another sensation (hearing, sight, smell, taste or touch), has been discovered. To the respondents’ mind, about 100 adjectives among this group mark the features that a speaker perceives on touch (the temperature parameters of objects, texture of their surface, consistency, presence or absence of moisture, etc.). The purpose of our study was to identify correlations between the data obtained in the psycholinguistic experiment and the lexicographic description of the corresponding adjectives carried out by traditional linguistic techniques. We used information from various dictionaries of Russian language, complemented by data from lexicographic sources of English, Ukrainian, Polish, and Italian. Two groups of adjectives (adjectives with the semantics of temperature and adjectives with the semantics of texture of their surface) have been examined in details. The general conclusion is that lexicographers mostly ignore the mention of the channel of perceptual information, often using synonyms or internal references in interpretations. This makes the lexicographic description of the adjectives little informative, does not reflect the psycholinguistic reality, does not give an idea of the significant role that belongs to the perceptual component in the semantic capacity of adjectives. References • Величковский Б. М., Зинченко В. П., Лурия А. Р. Психология восприятия. Москва: Из-во МГУ, 1973. • Кузнецов А.М. Некоторые теоретические проблемы семантики последних десятилетий // Лингвистические исследования в конце ХХ века: Сб. обзоров. Москва, 2000. С. 173–185.Колбенева М. Г., Александров Ю. И. Органы чувств, эмоции и прилагательные русского языка: Лингво-психологический словарь. Москва: Языки славянских культур, 2010. • Лаенко Л. В. Перцептивный признак как объект номинации. Воронеж : Воронеж. гос. ун-т, 2005. • Селиверстова О. Н. Роль информантов в процессе семантических исследований // Психолингвистические проблемы семантики / Отв. ред. А. А. Леонтьев и А. М. Шахнарович. Москва: Наука, 1983. С. 256-267. References (translated and transliterated) • Velichkovskiy, B. M., Zinchenko, V. P., Luriya, A. R. (1973). Psihologiya Vospriyatiya [Psychology of Perception]. Moscow: Moscow State University. • Kolbeneva, M. G., Aleksandrov, Yu. I. (2010). Organy chuvstv, emocii i prilagatelnye russkogo yazyka: Lingvo-Psihologicheskij Slovar [Organs of Senses, Emotions and Adjectives of the Russian Language]. Moscow: Yazyki slavyanskih kultur. • Kuznecov, A.M. (2000). Nekotorye teoreticheskie problemy semantiki poslednih desyatiletiy [Some theoretical problems of semantics of recent decades]. Lingvisticheskie Issledovaniya v Kontse ХХ Veka. Moscow, 173-185. • Layenko, L. V. (2005). Perceptivny Priznak kak Obyekt Nominatsii [Perception Feature as an Object of Nomination]. Voronezh: Voronezh State University. • Seliverstova, O. N. (1983). Rol’ informantov v processe semanticheskikh issledovanij [The informants’ role in the process of semantic study]. In: Psiholingvisticheskiye Problemy Semantiki, (pp. 256-267). A. A. Leontyev, A. M. Shahnarovich, (Eds.). Moscow: Nauka Джерела • АСРЯ – Активный словарь русского языка. Отв. ред. акад. Ю. Д. Апресян. М.: Языки славянской культуры. Т. 1, 2014. Т. 2, 2014. • БАС – Словарь современного русского литературного языка в 17 т. М. – Л.: Из-во АН СССР, 1950-1967. • Дм. – Толковый словарь русского языка под ред. Д. Дмитриева. М.: Астрель. 2003. • Ефр. – Ефремова Т.Ф. Новый словарь русского языка: Толково-словообразовательный. М.: Русский язык, 2000. Т. 1: А-О., Т. 2: П-Я. Режим доступа: http://efremova-online.ru/ • МАС – Словарь русского языка. В 4-х томах / Под ред. А.П. Евгеньевой. М. : Русский язык, 1985-1988. • САР – Словарь Академии Российской, по азбучному порядку расположенный. В 6-и частях. СПб., 1806-1822. • СУМ – Словник української мови : в 11-ти т. К. : Наукова думка, 1970-1980. • ОШ – Ожегов С. И., Шведова Н. Ю. Толковый словарь русского языка: 4-е изд., дополн. М.: ООО «А Темп», 2006. • Collins – The Collins English Dictionary. Retrieved from http://www.collinsdictionary.com • Dorosz. – Słownik języka polskiego pod red. W. Doroszewskiego. Retrieved from: http://sjp.pwn.pl/doroszewski/lista • Hornby – Hornby A. S. The Oxford Advanced Learner’s Dictionary of Current English. V. 1, 2. М.: Рус. язык, 1982. • Longman – The Longman Dictionary of Contemporary English. Retrieved from https://www.ldoceonline.com/ • Zing – Zingarelli, Nicola. Vocabolario della lingua italiana: decima edicione. Bologna, 1973. Sources • Slovar sovremennogo russkogo literaturnogo yazyka v 17 t. (1950—1967) M. L.: Iz-vo AN SSSR,Aktivnyj slovar russkogo yazyka. (2014). Yu. D. Apresyan, Ed. Moscow: Yazyki slavyanskoj kultury. V. 1, V. 2. • Tolkovyj slovar russkogo yazyka. (2003). D. Dmitriev, Ed. Moscow: Astrel. • Efremova T.F. (2000). Novyj slovar russkogo yazyka: Tolkovo-slovoobrazovatelnyj. Moscow: Russkiy Yazyk, 2000. T. 1: A-O. T. 2: P-Ya • Slovar russkogo yazyka. (1985-1988). V 4-h tomah. A.P. Evgeneva, Ed. Moscow: Russkij Yazyk. • Slovar Akademii Rossijskoj, po azbuchnomu poryadku raspolozhennyj. (1806—1822). 6 Volumes. S.-Petersburg. • Slovnyk ukrayinskoyi movy (1970-1980). 11 Volumes. Kyiv: Naukova Dumka. • Ozhegov S. I., Shvedova N. Yu. (2006). Tolkovyj slovar russkogo yazyka: 4-e izd., dopoln. Moscow: A Temp Ltd. • Collins – The Collins English Dictionary. Retrieved from: http://www.collinsdictionary.com • Dorosz. – Słownik języka polskiego pod red. W. Doroszewskiego. Retrieved from: http://sjp.pwn.pl/doroszewski/lista • Hornby — Hornby A. S. (1982). The Oxford Advanced Learner’s Dictionary of Current English. V. 1, 2. Moscow: Rysskiy Yazyk. • Longman – The Longman Dictionary of Contemporary English. Retrieved from: https://www.ldoceonline.com/ • Zing – Zingarelli, N. (1973). Vocabolario della lingua italiana: decima edicione. Bologna.